Estimation of Factors Affecting Income Traditional Fishermen - Darfiana Darfiana (Bulletin of Economic Studies (BEST), 2021)
The coastal area of East Sebatik District, Nunukan Regency has considerable marine and fishery potential in the fisheries sub-sector, especially marine fish catching, the development of capture fisheries production. This article tries to describe some of the determinants of fishermen's income in Tanjung Harapan Village, East Sebatik District. The type of research used in this research is quantitative research, with an explanatory approach. This primary data was obtained from a questionnaire distributed to respondents, namely fishermen in Tanjung Harapan Village, then the data was processed using the Excel program and then processed using the Eviews 9 application with the multiple linear regression analysis method. The results showed that the cost of fuel oil, the number of workers, technology, and time at sea had a positive and significant effect on the income of fishermen in Tanjung Harapan Village. Meanwhile, work experience has a positive but not significant effect on fishermen's income. The results of the research are expected to be useful in formulating policies and strategies to increase the income of fishermen in Tanjung Harapan Village, East Sebatik District.Keywords: Fisherman Income, Fishery Technology, East Sebatik